2022
DOI: 10.3389/fmats.2022.986011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coconut shell nanopowder reinforcement in the development of palm fiber composites

Abstract: Lightweight materials are being employed in aeronautical and automobile industries for high strength, lower weight, and energy consumption. Attention is needed to control pollution through the usage of harmful synthetic composites globally. In this work, coconut shell nanofillers are reinforced in the development of various palm fiber (leaf stalk, leaf sheath, leaf-spine, and fruit) composites using the hand layup technique. Mechanical and morphological effects of the addition of nano-coconut-shell-powder to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Similarly, for hemp NFRP, the thermal conductivity and resistivity values are found as 0.122702 W/mK and 0.098422 m 2 /mK. Te comprehensive experimental test based outcomes of thermal conductivity and resistivity are revealed in Figure 9 [2, [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, for hemp NFRP, the thermal conductivity and resistivity values are found as 0.122702 W/mK and 0.098422 m 2 /mK. Te comprehensive experimental test based outcomes of thermal conductivity and resistivity are revealed in Figure 9 [2, [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Test Resultsmentioning
confidence: 99%
“…Validate the experimental results and the computational analysis performed on the experimental test specimen. Based on the low error percentage, a computational analysis on the exhaust pipe is performed, and a grid convergence study is performed to improve the accuracy of the results [2,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. 1, it can be observed that Kenaf, Sisal, and cotton fbres have much lower thermal conductivity values in comparison to the other types of fbres.…”
Section: Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of multiple point cutting instruments in the manufacturing industry cannot be overstated. They are used to create parts and products with high precision, accuracy, and quality, which are crucial in many sectors such as aerospace, automotive, medical, and defense [3]. Different point cutting apparatuses play a imperative part in cutting edge machining operations, giving effective and exact fabric evacuation from work pieces.…”
Section: Introductionmentioning
confidence: 99%